2015
DOI: 10.1152/jn.01054.2014
|View full text |Cite
|
Sign up to set email alerts
|

Diverse cortical codes for scene segmentation in primate auditory cortex

Abstract: The temporal coherence of amplitude fluctuations is a critical cue for segmentation of complex auditory scenes. The auditory system must accurately demarcate the onsets and offsets of acoustic signals. We explored how and how well the timing of onsets and offsets of gated tones are encoded by auditory cortical neurons in awake rhesus macaques. Temporal features of this representation were isolated by presenting otherwise identical pure tones of differing durations. Cortical response patterns were diverse, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 109 publications
(103 reference statements)
9
21
1
Order By: Relevance
“…Prior studies indicate that the synchronized response duration or sound encoding time increases with increasing sound burst duration in A1 (Malone et al, 2015) and non-primary cortex (Lee et al, 2016) providing a potential neural code for temporal shape in the sound envelope. The "encoding time" corresponds to the time window over which a neuron conveys information about an ongoing sound and it can be quantified as a spike-timing variance (Theunissen and Miller, 1995;Chen et al, 2012) or alternatively as the duration of the response measured in the period histogram; that is, the histogram that is synchronized to the sound (Malone et al, 2015). Here we use the latter approach to examine how spiking patterns change throughout the duration of a sound burst by plotting the population response histogram and examine whether similar principles hold for non-primary cortices (see Materials and Methods; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies indicate that the synchronized response duration or sound encoding time increases with increasing sound burst duration in A1 (Malone et al, 2015) and non-primary cortex (Lee et al, 2016) providing a potential neural code for temporal shape in the sound envelope. The "encoding time" corresponds to the time window over which a neuron conveys information about an ongoing sound and it can be quantified as a spike-timing variance (Theunissen and Miller, 1995;Chen et al, 2012) or alternatively as the duration of the response measured in the period histogram; that is, the histogram that is synchronized to the sound (Malone et al, 2015). Here we use the latter approach to examine how spiking patterns change throughout the duration of a sound burst by plotting the population response histogram and examine whether similar principles hold for non-primary cortices (see Materials and Methods; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). A similar approach has been used previously to quantify temporal response patterns in inferior colliculus (Zheng and Escabí, 2008) and cortex (Malone et al, 2007(Malone et al, , 2015. The period histogram is constructed by aligning the spike-time histogram relative to the sound onset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work uncovered two major response types in Zone 1 and Zone 2 with "transient" and "sustained" responsivity to sentences. Such "phasic" and "tonic" response types have been observed in single unit electrophysiological recordings throughout the auditory system, including the temporal lobe auditory cortex (Eggermont, 2001;Malone et al, 2015;Romanski et al, 1999), auditory brain stem (Atencio et al, 2012;Zheng and Escab, 2008), and even prefrontal cortex, where they may be involved in decision making and object identification within the "ventral stream" (Bizley and Cohen, 2013;Romanski and Goldman-Rakic, 2002;Romanski et al, 1999;Tsunada et al, 2016). Previous studies, however, have not clearly documented the spatial segregation of these response types in auditory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The auditory cortex encodes various temporal information (Brasselet et al, 2012;Fishman and Steinschneider, 2009;Ince et al, 2013;Malone et al, 2010,). This capability may benefit from the separated neuron populations which selectively respond to different temporal features (Malone et al, 2015;Hamilton et al, 2018). One of the lesion studies suggested that InsP may involve in auditory temporal processing (Bamiou et al, 2006).…”
Section: Basic Auditory Response Properties In the Supra-temporal Arementioning
confidence: 99%